Immunomodulatory activity of Pepolo (Bischofia javanica Blume) stem bark ethanolic extract in Staphylococcus aureus-stimulated macrophages and anticancer activity against MCF-7 cancer cells - Yuliet Susanto, Rifda Nurfajar, Sindia, Khildah Khaerati, Vienna Saraswaty (Journal of Applied Pharmaceutical Science, 2022)
Pepolo (Bischofia javanica Blume) is an Indonesian native plant whose stem bark is widely used as a traditional medicine for various diseases. Therefore, this study aims to determine the chemical profile of the secondary metabolites of the Pepolo stem bark (PSB) extract and its effectiveness as a potential immunomodulatory and anticancer agent. The PSBs were extracted by a reflux technique with 96% v/v ethanol as solvent. The immunomodulatory activity of the PSB extract was evaluated based on its effect on the macrophages of BALB/C mice, while the cytotoxicity and anticancer potential were observed as the PSB extract response on brine shrimp lethality test and MCF-7 cancer cells, respectively. The chemical profiles of the secondary metabolites were analyzed using a Liquid Chromatography- Mass Spectrometry/Mass Spectrometry instrument. The result is that the PSB extract showed its potential as an immunomodulatory and anticancer agent. The toxicity evaluation showed that the PSB extract was classified as a toxic material. More importantly, the PSB extract showed an activity against MCF-7 cancer with lethal concentration 50% (LC50) values of 68.46 μg/mL and an inhibition concentration 50% (IC50) of 362.36 μg/mL, respectively. The chemical evaluation suggested that the terpenoid and polyphenolic compounds are responsible for the immunomodulatory and anticancer mechanisms. In summary, our work showed that the PSB extract is a potential alternative source for the treatment of breast cancer and supports the immune response.
Keywords: Anticancer, immunomodulator, Pepolo stem bark, BSLT, MCF-7, LC-MS/MS